Hierarchical chrysanthemum-flower-like carbon nanomaterials grown by chemical vapor deposition. (26th January 2016) - Ding, Er-Xiong; Geng, Hong-Zhang; Wang, Jing; Luo, Zhi-Jia; Li, Guangfen; Wang, Wen-Yi; Li, Lin-Ge; Yang, Hai-Jie; Da, Shi-Xun; Wang, Jie; Jiang, Hua; Kauppinen, Esko I
Abstract: Novel hierarchical chrysanthemum-flower-like carbon nanomaterials (CFL-CNMs) were synthesized by thermal chemical vapor deposition based on acetylene decomposition. A scanning electron microscope and a transmission electron microscope were employed to observe the morphology and structure of the unconventional nanostructures. It is found that the CFL-CNMs look like a blooming chrysanthemum with a stem rather than a spherical flower. The carbon flower has an average diameter of 5 μ m, an average stem diameter of 150 nm, branch diameters ranging from 20 to 70 nm, and branch lengths ranging from 0.5 to 3 μ m. The morphologies of the CFL-CNMs are unlike any of those previously reported. Fishbone-like carbon nanofibers with a spindle-shaped catalyst locating at the tip can also be found. Furthermore, the catalyst split was proposed to elucidate the formation mechanism of CFL-CNMs. A large and glomerate catalyst particle at the tip of the carbon nanofiber splits into smaller catalyst particles which are catalytic-active points for branch formation, resulting in the formation of CFL-CNMs.